SLPs Perspective on Stuttering Intervention through Technological Rehabilitation - Aziz, Faiza; Zahra, Syeda Mariam; Hassan, Hafsa; Riaz, Mamona; Javed, Anika; Irum, Aleena (Journal of Liaquat University of Medical & Health Sciences, 2025)
Objective: To investigate the practising patterns of speech-language pathologists regarding technological rehabilitation for stuttering intervention. Methodology: This study employed a cross-sectional, quantitative design using a 5-point Likert scale. The data were collected from January to June 2023 at Riphah International University. This study employed convenience sampling techniques. The research focused on finding tools and Software for pattern-based therapy techniques that utilize technological rehabilitation to improve the therapy process. The Data was collected from Speech Therapist Online through Google Forms and Riphah Rehabilitation Clinic. The inclusion criteria consist of only qualified Speech and Language Pathologists (SLPs) who use technological rehabilitation in their therapies; any other disorders and comorbid disabilities were excluded. Data analysis was conducted through SPSS Version 21. Results: The study sample consisted of 242 respondents, including qualified speech-language pathologists (SLPs) and rehabilitation therapists from public and private hospitals and clinics. Results of the study show the highest frequency of Using technological rehabilitation is beneficial for patients (117), Use of Technology helps to overcome lifelong challenges (111), Use of Software and devices in stuttering therapy (120), and Cost of Software is high (100) Conclusion: The technological Rehabilitation in stuttering therapy; the majority of respondents give preference to using it, and they also recommend it to their peers. A similar number of respondents believe that technological rehabilitation needs Software and devices that are costly, but they are hopeful about its future. The research emphasizes the call for future research on low-cost, accessible technology tools and longitudinal studies to measure their effectiveness.